(3GdJYdd HQShe GdCSfGO HYO GfJbGd Cgd GdefRd hGdfGOs - (3eMeO Hf CMeO Hf eMeO Hf eMeO Hf Ydj Hf ZGRj GdYKeGfj GdecfGSj , GHf ZGRj , CHh YHO Gddg,J (B919 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdMeO ddg SHMGfg Mb MeOg CeG HYO abO hUd EdjfG ef eOjfI JdeSGf CefgG Gddg JYGdi CQHYI cJH s
(3BNQgG (B:s
(3aai TQHI dh cGf Yde SajJce hde CNa Yfce Pdc GdYde HGdPNQ Cf GdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B226s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMOjK h GdeUWdMs